2017
DOI: 10.4038/slja.v25i1.8169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ease of intubation using C-MAC Vs Macintosh laryngoscope in patients with the application of manual inline axial stabilization - A randomized comparative study

Abstract: Background and Aims: Endotracheal intubation in patients with cervical spine injury can be challenging particularly in the presence of manual in line stabilization. Video laryngoscopes can be used in these situations as their popularity is growing in the management of difficult airway and recently Difficult Airway Society (DAS) has included these devices in their algorithm.Methods: Sixty ASA 1 and 2 patients with normal airway requiring general anesthesia with endotracheal intubation were recruited for this ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
0
1
1
Order By: Relevance
“…where the hemodynamic response among the patients intubated with Macintosh and C-MAC video laryngoscope were found to be more or less similar. [11,12] Report presented by Sarkar et al however justified our result mean heart rate and blood pressure among the patients of the direct laryngoscope group was found to be more than 2 fold higher in comparison to those intubated with video laryngoscope. [13] In this study no significant difference in the level of the percentage of oxygen saturation (SpO2) was observed among the patients intubated with Macintosh and C-MAC video laryngoscope.Similar results were also reported previously by Mogahed et [7,13,14] However, in a study by Goksu et al, it was reported that the number of patients with oxygen saturation level below 90% was greater among the patient's group intubated with Macintosh laryngoscope in comparison to those intubated with C-MAC video laryngoscope which was inconsistent with our study.…”
Section: Resultscontrasting
confidence: 39%
“…where the hemodynamic response among the patients intubated with Macintosh and C-MAC video laryngoscope were found to be more or less similar. [11,12] Report presented by Sarkar et al however justified our result mean heart rate and blood pressure among the patients of the direct laryngoscope group was found to be more than 2 fold higher in comparison to those intubated with video laryngoscope. [13] In this study no significant difference in the level of the percentage of oxygen saturation (SpO2) was observed among the patients intubated with Macintosh and C-MAC video laryngoscope.Similar results were also reported previously by Mogahed et [7,13,14] However, in a study by Goksu et al, it was reported that the number of patients with oxygen saturation level below 90% was greater among the patient's group intubated with Macintosh laryngoscope in comparison to those intubated with C-MAC video laryngoscope which was inconsistent with our study.…”
Section: Resultscontrasting
confidence: 39%
“…The characteristics of the included studies are shown in Table 1 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsunclassified